INDONESIA’S UPSTREAM PETROLEUM GOVERNANCE REFORM: WHICH MODEL IS CONSTITUTIONAL ENOUGH? - Dwiesta, Afghania (UI Scholars Hub, 2018)
The Indonesian Constitutional Court abruptly annulled provisions regarding the function of BP Migas as state representative in managing upstream oil and gas operations in Indonesia, declaring it unconstitutional. Apparently, the Court was convinced that exercising absolute state control over hydrocarbon operations would give the utmost benefit to the people. This research argues that in achieving such goals, a state must be able to create strong administrative infrastructure and regulatory regime capable of controlling and supervising hydrocarbon operations in accordance with both national and international oil fields. Using a comparative study method with secondary data collection, this research observes Norway’s, Mexico’s, Malaysia’s, and Russia’s experiences as its underlying methodology. It examines the Court’s interpretation of “control” and “ownership” over hydrocarbon operations and provides possible solutions for the most effective and suitable institutional design for BP Migas’ replacement. Finally, it concludes that to fulfill the constitutional mandate, the government’s ability to manage oil and gas sector depends on how much it is willing to consistently: (i) implement good corporate governance among related stakeholders so as to lessen political interference in the decision-making process, and (ii) maintain the balance of ex ante procedures and the post ante monitoring system in the adopted institutional model.